An exploratory examination of patient and parental self‐efficacy as predictors of weight gain in adolescents with anorexia nervosa. Issue 7 (25th March 2015) - Byrne, Catherine E.; Accurso, Erin C.; Arnow, Katherine D.; Lock, James; Le Grange, Daniel
ABSTRACT Objective To determine whether increases in adolescent or parental self‐efficacy predicted subsequent weight gain in two different therapies for adolescent anorexia nervosa (AN). Method Participants were 121 adolescents with AN (M = 14.4 years, SD = 1.6), from a two‐site randomized clinical trial for family‐based treatment (FBT) and individual adolescent focused therapy (AFT). Both adolescent and parental self‐efficacy were assessed at baseline and sessions 2, 4, 6, and 8. Adolescent self‐efficacy was assessed using a generic measure of self‐efficacy, while parental self‐efficacy was assessed using a measure specific to the recovery of an eating disorder. Weight was assessed at baseline, sessions 1 through 8, and end of treatment. Mixed‐effects models were used to evaluate the relation between patient and parent self‐efficacy and subsequent weight gain, controlling for weight at the previous time point. Results For families who received FBT, greater within‐treatment increases in parental self‐efficacy predicted greater subsequent adolescent weight gain compared to those who received FBT with lesser change in parental self‐efficacy and those who received AFT. Interestingly, adolescent self‐efficacy did not significantly predict subsequent weight gain. Discussion Greater increases in parental self‐efficacy predicted significantly greater subsequent weight gain for adolescents who received FBT, but the same was not true for adolescents who received AFT. Neither overall level nor change in adolescent self‐efficacy significantly predicted subsequent weight gain in either treatment group. These findings emphasize the importance of increasing parental self‐efficacy in FBT in order to impact adolescent weight outcomes. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:883–888)